Taxonomy Complexity of Some Tyrrhenian Endemic Limonium Species Belonging to L. multiforme Group (Plumbaginaceae): New Insights from Molecular and Morphometric Analyses - Duilio Iamonico; Olga De Castro; Emanuela Di Iorio; Gianluca Nicolella; Mauro Iberite (Plants, 2022)
The delimitation of Limonium taxa is highly complicated due to hybridization, polyploidy, and apomixis. Many “microspecies” were described and aggregated into groups, most of which are still poorly known from both molecular and morphological points of view. The aim of this study is to investigate four endemic species from the Tyrrhenian coast of central Italy and the Ponziane Archipelago belonging to the L. multiforme group (L. amynclaeum, L. circaei, L. pandatariae, and L. pontium) by means of molecular and morphometric analyses. Molecular data by sequencing ITS and three plastid markers and morphometric data highlight new information about the taxonomy of these taxa so as to reduce them into a single specific entity. In fact, the better taxonomic choice is to consider the populations studied as part of a single species, i.e., Limonium pontium. Three subspecies are recognized, i.e., subsp. pontium [= L. circaei = L. amynclaeum; from Circeo to Gianola localities (excluding Terracina) and from islands Ponza, Palmarola, Zannone, and Santo Stefano], subsp. pandatariae comb. et stat. nov. (from island of Ventotene), and subsp. terracinense subsp. nov. (from Terracina).